2011
DOI: 10.1182/blood-2011-06-363648
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxin (Stx)1B and Stx2B induce von Willebrand factor secretion from human umbilical vein endothelial cells through different signaling pathways

Abstract: IntroductionIngestion of food contaminated with Shiga toxin (Stx)-producing Escherichia coli, such as strain O157:H7, can cause bloody diarrhea that develops into diarrhea-associated hemolytic uremic syndrome (D ϩ HUS) that is characterized by acute renal failure, thrombocytopenia, and microangiopathic hemolytic anemia. D ϩ HUS is the most common cause of acute renal failure in children and is fatal in ϳ 3%-5% of cases. 1 Several mechanisms seem to influence the course of tissue injury by Stx. Stx-producing E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Stxbp5 mRNA was expressed in murine tissues, including lung, spleen, and aorta, as measured by quantitative real-time PCR (qPCR; Figure 1B). Stxbp5 mRNA was also found ECs through discrete signaling pathways (37)(38)(39)(40)(41)(42)(43)(44). However, the detailed mechanisms controlling the endothelial SNARE machinery are not fully known.…”
Section: Resultsmentioning
confidence: 99%
“…Stxbp5 mRNA was expressed in murine tissues, including lung, spleen, and aorta, as measured by quantitative real-time PCR (qPCR; Figure 1B). Stxbp5 mRNA was also found ECs through discrete signaling pathways (37)(38)(39)(40)(41)(42)(43)(44). However, the detailed mechanisms controlling the endothelial SNARE machinery are not fully known.…”
Section: Resultsmentioning
confidence: 99%
“…However, purified B subunits of Stx1 and Stx2 have been reported to induce secretion of von Willebrand factor by human endothelial cells and to contribute to thrombotic microangiopathy in mice (35). Interestingly, this appeared to involve activation of distinct signaling pathways by Stx1B and Stx2B, dependent upon protein kinase C␣ and protein kinase A, respectively (36). Thus, Stx B subunits may play a direct role in the endothelial injury that is the hallmark of the systemic complications of STEC disease in humans.…”
Section: Discussionmentioning
confidence: 99%
“…by guest www.bloodjournal.org From more importantly, we identify for the first time a phosphorylation/ dephosphorylation target activated in the course of cAMP-triggered VWF secretion. Although evidence for a role of PKA in cAMPdependent VWF secretion has been obtained through inhibitor experiments, 16,17,40,41 PKA substrates in this pathway are not known. Although counterintuitive at a first glance, we show that PKA (indirectly) triggers a dephosphorylation of AnxA2, thereby promoting AnxA2-S100A10 complex formation that in turn is required for efficient WPB exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Future experiments are needed to reveal whether this pathway also operates in the recently described PKA-dependent release of VWF that is triggered by Shiga toxin 2B and occurs without elevation of intracellular cAMP levels. 17 Previous in vitro approaches identified PKC phosphorylation sites in the N-terminal domain of AnxA2 that affect the stability of the AnxA2-S100A10 complex, 32 and a recent study revealed a PKCdependent serine phosphorylation of AnxA2 in endothelial cells that induced a dissociation from S100A10. 24 Thus, PKC seems to be primarily responsible for complex-destabilizing serine phosphorylation in AnxA2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation